SPECTRAL ALBEDO AND TRANSMITTANCE OF SNOW CONTAINING IMPURITIES - アオキ, テルオ; アオキ, タダオ; フカボリ, マサシ; イイダ, ハジメ; AOKI, Teruo; AOKI, Tadao; FUKABORI, Masashi; IIDA, Hajime (National Institute of Polar Research, 1995)
P(論文) Spectral albedo and transmittance of snow are investigated by field observation and a multiple scattering model. Observations were carried out on a snow field with enough snow depth (∿7m) at Murodo (36°34′30″N, 137°36′00″E, H=2440m) in Northern Alps of Japan in April 1994. The spectral albedo was observed with a grating type spectrometer at wavelengths from 0.35 to 2.5μm. In this time, the snow surface was covered with an ice crust of 1-2cm thickness containing impurities, and comparatively pure snow was below it. Spectral albedos for snow surfaces with ice crust and without it (removed artificially) agree with the results of a multiple scattering model for snow containing impurities with radius of 500μm and for pure snow with radius of 100μm, respectively. On the other hand, transmittance inside the snow was observed by an optical fiber probe with a spectrometer. The observed transmittances of both snow with surface ice crust and without it at the depth of 15-18cm from the surface had a spectral distribution with peak in the wavelength region from 0.5 to 0.6μm. However, snow transmittance by a multiple scattering model for pure snow becomes a spectral distribution with peak in the wavelength region from 0.45 to 0.50μm as the snow depth increases. This suggests that only a small amount of impurity contained in snow without surface ice crust affects the transmittance inside the snow. departmental bulletin paper